2006
DOI: 10.1007/bf03021583
|View full text |Cite
|
Sign up to set email alerts
|

Mise à jour basée sur des données probantes: Améliore-t-on le comportement des enfants par une prémédication au midazolam par la bouche?

Abstract: Premedication with midazolam 0.5 mg x kg(-1) po administered 20-30 min preoperatively, is effective in reducing both separation and induction anxiety in children (grade A recommendation), with minimal effect on recovery times. However improved postoperative behavioural outcomes in the postanesthesia care unit, or at home cannot be predicted on a consistent basis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(52 citation statements)
references
References 31 publications
4
47
0
1
Order By: Relevance
“…Midazolam is safely used in outpatient pediatric groups for effective sedation and reduced anxiety. It has a minimal effect on recovery time [7]. Both midazolam and ketamine have been used for sedation in pediatric patients for different procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Midazolam is safely used in outpatient pediatric groups for effective sedation and reduced anxiety. It has a minimal effect on recovery time [7]. Both midazolam and ketamine have been used for sedation in pediatric patients for different procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Midazolam can be given for premedication to reduce oxygen consumption. [10] Infective endocarditis is a serious concern and prophylaxis must be given with antibiotics. Full blood count and coagulation profile should always be requested.…”
Section: Discussionmentioning
confidence: 99%
“…(10) Cox et al concluded that oral midazolam is effective in reducing both separation and induction anxiety, which correlates with our study. (11) Induction score was excellent in 54% children with midazolam compared to 44% in ketamine group. Patel and Meakin also reported greater anxiolysis after oral midazolam than after a combination of diazepam and droperidol or trimeprazine.…”
Section: Discussionmentioning
confidence: 99%